Methodological Insights Accounting talk: developing conversation analysis in accounting research. Issue 6 (3rd February 2022) - Baker, Max; Andrew, Jane; Roberts, John
Abstract : Purpose: This paper proposes a research method for analysing talk about accounting concepts, systems and numbers. The authors argue that studying accounting talk in situ is a fruitful way to understand both the role accounting plays in the framing of relationships between individuals and the associated emotional content of these exchanges. As such, the authors argue that conversation analysis (CA) is a useful complement to interviews in qualitative research. Design/methodology/approach: The authors introduce a specific approach to CA called positioning theory, which captures the linguistic and emotional subtleties embedded within interpersonal interactions, and the way accounting impacts and mediates these relations through measuring, assessment and control. The authors draw on one particularly animated conversation about accounting in a manufacturing company. The conversation was a largely emotional and animated exchange between individuals where talk about accounting was imbued with metaphors, violence, sex and humour. Findings: While participants in conversations may appear to draw on similar forms of language and expression, CA allows researchers to see that the meaning of these shared expressions change based on who is saying them, whom they are saying them to and how they are saying them. Dissecting conversations as they unfold, offers a more nuanced and multifaceted understanding of accounting as central to the social fabric of organisational life. Originality/value: As opposed to interviews, which often suffer from the rationality of hindsight (referred to as retrospective rationality), CA captures the unfolding nature of accounting talk in real-time–not upon reflection.